Brain transcriptome analysis of snakehead (Channa argus) under starvation and satiation conditions and identification of differentially expressed gene response to feeding regulation - Xiao-yan Jin; Xiu-mei Chen; Gui-liang Guo; Li Sun; Xue-qin Wu; Yun-jie Lin; Xiao-tian Niu; Yi-di Kong; Min Li; Gui-qin Wang (Aquaculture Reports)
The Channa argus (C. argus), a warm-water piscivorous fish, is an important economic breed with high nutritional value, but there are some problems such as difficulty in domestication and feeding. In order to solve the problem of feeding and to better understand the regulation of feeding at the molecular level, RNA sequencing (RNA-seq) was sequenced in the brains of wild and cultured C. argus under starvation and satiation. The groups included the wild C. argus starvation group (WST), the wild C. argus satiation group (WSA), the cultured C. argus starvation group (CST) and the cultured C. argus satiation group (CSA). For the pairwise comparisons of these four groups, the number of differential genes was 43 (WST vs. WSA, 16 up-regulated and 27 down-regulated genes), 96 (CST vs. CSA, 44 up-regulated and 52 down-regulated), 193 (WST vs. CST, 31 up-regulated and 162 down-regulated genes), 489 (WSA vs. CSA, 256 up-regulated and 233 down-regulated genes), respectively. Differential gene functional enrichment analysis revealed that several pathways were highlighted, including PI3K-Akt signaling pathway, adipocytokine signaling pathway, estrogen signaling pathway, melanogenesis, and cyclic adenosine monophosphate (cAMP) signaling pathway in the cultured starvation group and the cultured satiation group. In the adipocytokine signaling pathway, down-express gene is agouti-related peptide (AgRP), the cAMP signaling pathway showed up-regulated genes such as chromogranin A (CGA), luteinizing hormone beta polypeptide (LHB), thyroid stimulating hormone beta (THSB), and follicle stimulating hormone beta (FSHB). These pathways and genes may play important roles in the regulation of energy metabolism and feeding. Quantitative real-time PCR of the starvation, satiation, and lipopolysaccharide (LPS) treatment groups showed that the differential expression changes of appetite-related and immune-related genes matched the trend of differential expression of the transcriptome counterparts. This study provides the basic data for the regulation of feeding and the molecular mechanisms related to feeding.